As origens da Embraer The origins of Embraer - Maria Cecilia Spina Forjaz (Tempo Social, 2005)
Este artigo analisa a criação das organizações que deram origem à Embraer, isto é, o Ministério da Aeronáutica, o Centro Tecnológico de Aeronáutica (CTA) e o Instituto Tecnológico da Aeronáutica (ITA), fundados nos anos de 1940 e 1950. Essas organizações criaram as condições para a fundação da empresa estatal em 1969. São analisadas as suas relações com o projeto estratégico de defesa nacional da Aeronáutica. The article analyses the emergence of organizations that originated Embraer, i.e., the Ministry of Aeronautics, the Aeronautics Technological Center (CTA) and the Aeronautics Technological Institute (ITA), founded in the 1940's and 1950's. These organizations made it possible for the state enterprise to come into existence in 1969. This paper analyses the Embraer's involvement with the Aeronautics' national defense strategic project.